PRACTICAL KNOWLEDGE, ATTITUDES, AND PRACTICES IN POST-OPERATIVE WOUND CARE AT THE CENTRAL DERMATOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aimed to assess the knowledge, attitude, and practice (KAP) of patients after surgery for ingrown toenail (onychocryptosis) with two specific objectives: (1) to describe the clinical characteristics of patients with ingrown toenail, and (2) to evaluate their KAP regarding postoperative wound care.Methods: A pre–post intervention study was conducted on 100 patients at the National Hospital of Dermatology and Venereology from April 1, 2024 to April 1, 2025. The questionnaire included five parts: general information, knowledge (10 questions), attitude (5 questions), practice (5 questions), and support needs (3 questions). Data were analyzed using SPSS 20.0 and R 4.1.0.Results: Before intervention, the proportion of patients with adequate KAP was limited (good knowledge: 5%, positive attitude: 6%, good practice: 33%). After intervention, mean scores improved significantly: knowledge increased from 3.97±2.29 to 7.71±1.26, attitude from 18.01±1.57 to 22.81±1.66, and practice from 3.12±0.88 to 4.21±0.74 (p
Keywords: Knowledge, Attitude, Practice; Postoperative care; Ingrown toenail; Intervention.